1983
DOI: 10.1128/aac.23.3.379
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiplaque activity of octenidine dihydrochloride (WIN 41464-2) against preformed plaques of selected oral plaque-forming microorganisms

Abstract: The antibacterial activity of octenidine dihydrochloride (WIN 41464-2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
(37 reference statements)
1
31
0
2
Order By: Relevance
“…In earlier studies, the MICs of OCT and CHG against a variety of test bacteria were quite similar (2,20). In this study, the bactericidal activity of OCT was superior to that of CHG, especially against Staphylococcus aureus and Streptococcus pyogenes.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In earlier studies, the MICs of OCT and CHG against a variety of test bacteria were quite similar (2,20). In this study, the bactericidal activity of OCT was superior to that of CHG, especially against Staphylococcus aureus and Streptococcus pyogenes.…”
Section: Resultsmentioning
confidence: 65%
“…Earlier studies demonstrated its activity against dental plaque microflora (16,20,21); this study shows that OCT is also effective against skin microflora.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…7,11 Octenisept was demonstrated to have broad-spectrum antimicrobial effects against both Gram-positive and Gramnegative bacteria, fungi and several viral species, 14 and the efficacy of octenidine was reported against dental plaqueassociated bacteria when compared with CHX. 25,26 Octenisept was chosen as a test solution in this study after the publication of reports that it was used as a root canal dressing material and had antibacterial activity against E. faecalis in root canal and dentine after one minute. 13 There are a few studies that evaluate the residual antimicrobial activity of the immersion of gutta-percha into different solutions.…”
Section: Discussionmentioning
confidence: 99%
“…8 Octenidine hydrochloride (OCT) Octenidine (Schulke & Mayr GmbH, Norderstedt, Germany), is a bispyridine derivative, i.e., N,N-[1,10-decanediyldi-1(4H)-pyridinyl -4 pylidene] bis (1-octanamine) dihydrochloride a new bipyridine antimicrobial compound, has been developed as a potential antimicrobial/antiplaque agent for use in mouthwash formulations. 9 The existing data suggest that a mouthrinse containing 0.1% OCT may be capable of exerting beneficial clinical effects upon plaque accumulation and gingivitis. OCT used in the form of mouthrinse was reported to inhibit dental plaque and caries both in rats and humans.…”
mentioning
confidence: 99%